PENUMBUHAN WIRAUSAHA BARU PADA MAJELIS DA’WAH AL’ADNI - Sahroni, Sahroni; Susanto, Susanto; Sutoro, Moh.; Mukrodi, Mukrodi; Apriansyah, Muger (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service aims to raise new entrepreneurs in the Majlis Da’wah Al- ‘Adni. Issues raised regarding how to start a business properly and correctly. The method used in the implementation of this service is carried out in several activities, namely (a). The Preparation Phase includes: (1). Initial survey (2) Consolidation and determination of target locations, (3). Preparation of training materials / materials. The results of this activity are very beneficial for Majlis Da'wah Al-‘Adni in the growth of new entrepreneurs in terms of how to start a business to become MSMEs properly and correctly.